2011
DOI: 10.1007/s10653-011-9390-6
|View full text |Cite
|
Sign up to set email alerts
|

Lead contamination and its potential sources in vegetables and soils of Fujian, China

Abstract: Lead (Pb) contents and partition in soils collected from eleven vegetable-growing lands in Fujian Province, China, were investigated using a modification of the BCR (Community Bureau of Reference) sequential extraction procedure coupled with the Pb isotope ratio technique. Pb contents in Chinese white cabbage (B. Chinensis L.) grown on the lands for this study were also measured. Results showed that Pb concentrations in fifty samples of topsoil ranged from 456 to 21.5 mg kg(-1), with each mean concentration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…For Pb, the highest levels in vegetables generally occur where soil Pb levels are the highest (Bielinska, 2009; Huang et al, 2012; Jorhem et al, 2000; Moir and Thornton, 1989; Samsøe-Petersen et al, 2002). Some studies using sensitive methods for analyzing vegetable metals concentrations have indicated a near-linear relationship between soil Pb and vegetable Pb concentrations, so that bioconcentration factors (BCFs) could be estimated (e.g., 0.001, 0.002 and 0.05 for lettuce, potato and carrot [with peel], respectively) (Samsøe-Petersen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For Pb, the highest levels in vegetables generally occur where soil Pb levels are the highest (Bielinska, 2009; Huang et al, 2012; Jorhem et al, 2000; Moir and Thornton, 1989; Samsøe-Petersen et al, 2002). Some studies using sensitive methods for analyzing vegetable metals concentrations have indicated a near-linear relationship between soil Pb and vegetable Pb concentrations, so that bioconcentration factors (BCFs) could be estimated (e.g., 0.001, 0.002 and 0.05 for lettuce, potato and carrot [with peel], respectively) (Samsøe-Petersen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest that plant availability of Pb is correlated to particular Pb fractions extracted in the sequential extraction procedure [6]. However, previous research has shown that the bulk of the Pb in contaminated soils is extracted in the “reducible” or “oxide” fraction, a strongly acidic extractant (pH near 2) of the 4-step BCR method [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Whatever the method used (BCR or single extraction), the exchangeable fraction of Cd decreased with pH increase indicating lower exchangeability in alkaline soils. Huang et al [6] reported that in alkaline soils, Cd is mostly released from carbonate-and Fe-/Mn-oxide bound fractions.…”
Section: Comparison Of Labile Pools Estimated By Sequential Single Amentioning
confidence: 99%